Unlocking teachers' organizational citizenship behavior: exploring compensation in transmitting visionary leadership - Sulistiasih, Sulistiasih; Widodo, Widodo (Journal of Education and Learning (EduLearn), 2025)
For both organizational and personal life, especially for teachers in the context of schools, organizational citizenship behavior (OCB), is essential. Thus, this study investigates and creates a novel empirical model of the mediation mechanism of compensation on the relationship between visionary leadership and teachers' OCB. For this study, 230 private junior high school teachers in three Indonesian provinces Jakarta, West Java, and Banten were given Likert scale questionnaires. With survey methods and analyses by structural equation modeling (SEM) found a significant impact of visionary leadership and compensation on OCB, the substantial influence of visionary leadership on compensation, and the significant effect of visionary leadership on OCB through compensation. This evidence supports a novelty about visionary leadership, through compensation, affects teachers' OCB. It is in line with and confirms the results of previous research as the basis of this research and, at the same time, negates the conflicting results of previous research. Under these circumstances, the novel model offers a theoretical and practical contribution that necessitates thorough and critical debate prior to adoption, adaptation, or modification as a model for enhancing teachers' OCB through visionary leadership backed by compensation.